Study on surface electric field and ground nominal electric field of HVDC transimission line on slope terrain - Chenguang Gao; Yuanqing Liu; Jiangtao Zhao; Xirun Zhang; Wenyu Li; Hui Han; Jingchen Zhang (The Journal of Engineering, 2019)
In order to study the fast calculation method of a surface electric field of the arbitrary-quantity bundled conductor and a ground nominal electric field of the HVDC transmission line on slope terrain. Based on the basic principles of the image method, this paper deduces the calculation formula of the surface maximum electric field of the arbitrary-quantity bundled conductor and the ground nominal electric field of the HVDC transmission line with single bipolar horizontal arrangement over the slope terrain by making the reasonable approximation and equivalence to the actual situation. Compared with the finite element method, the results got from the formula proposed in this paper verify that these formulas are accurate and valid. The effects of slope inclination, pole–pole spacing of the conductor on the electric field of the conductor surface and the ground nominal electric field of the HVDC transmission line are analyzed and obtained. The results of research indicate that the inclination of the slope and the pole–pole spacing of the conductor have a great influence on the conductor surface electric field and the ground nominal electric field. When the HVDC transmission line is erected on the slope terrain, the formula proposed in this paper can provide references for circuit design and electromagnetic environment analysis.